Planning and developing a web-based intervention for active surveillance in prostate cancer: an integrated self-care programme for managing psychological distress - Hughes, Stephanie; Kassianos, Angelos P.; Everitt, Hazel A.; Stuart, Beth; Band, Rebecca (My University, 2022)
Objectives: To outline the planning, development and optimisation of a psycho-educational behavioural intervention for patients on active surveillance for prostate cancer. The intervention aimed to support men manage active surveillance-related psychological distress. Methods: The person-based approach (PBA) was used as the overarching guiding methodological framework for intervention development. Evidence-based methods were incorporated to improve robustness. The process commenced with data gathering activities comprising the following four components: • A systematic review and meta-analysis of depression and anxiety in prostate cancer • A cross-sectional survey on depression and anxiety in active surveillance • A review of existing interventions in the feld • A qualitative study with the target audience The purpose of this paper is to bring these components together and describe how they facilitated the establishment of key guiding principles and a logic model, which underpinned the frst draft of the intervention. Results: The prototype intervention, named PROACTIVE, consists of six Internet-based sessions run concurrently with three group support sessions. The sessions cover the following topics: lifestyle (diet and exercise), relaxation and resilience techniques, talking to friends and family, thoughts and feelings, daily life (money and work) and information about prostate cancer and active surveillance. The resulting intervention has been trialled in a feasibility study, the results of which are published elsewhere. Conclusions: The planning and development process is key to successful delivery of an appropriate, accessible and acceptable intervention. The PBA strengthened the intervention by drawing on target-user experiences to maximise acceptability and user engagement. This meticulous description in a clinical setting using this rigorous but fexible method is a useful demonstration for others developing similar interventions.
Keywords: Prostate cancer; Active surveillance; Psychological distress; Online intervention; Web-based intervention; Digital intervention; Self-management; Anxiety; Person-based approach